Relationship between Management Styles and Performances of Professional Athletes in Kwara State Colleges of Education, Nigeria - Ajadi, M. T.; Baba, D. A.; Sheu, A. A.; Ogungboye, R. O. (International Journal of Educational Management, 2022)
This study examined the relationship between management styles and performances of professional athletes in Kwara State Colleges of Education. The population for this study comprised of the director of sport, members of the sport committee, sport co-ordinator, athletes of Colleges of Education in Kwara State. One hundred and eighty respondents were randomly selected as sample for the study from three Colleges of Education in Kwara State. The instrument used for data collection for the study was a researcher structured questionnaire which was validated and tested with the use of test – re-test method. The reliability coefficient result of 0.76 was obtained. Pearson product moment correlation coefficient (r) was used to test the hypotheses generated at 0.05 alpha level of significance. The result showed that there was strong relationship between management styles adopted by managers and performances of professional athletes in Kwara State colleges of education.